Examining student work collaborative analysis of student learning - Johnson, Todd; Oppenheimer, Jim; Association for Supervision and Curriculum Development ([Alexandria, CA] : Association for Supervision and Curriculum Development, 2002)
Educators are now using student work as a vehicle to reflect in groups upon their own teaching practices and to change or develop new teaching strategies to help all students learn. This video series examines this process and several specific methods of how educators critically review student work and assignments in collaborative teams.
Title from title screen
Editor, Steve Wegrich ; director of photography, Terry McArdie
Keywords: Academic achievement -- Evaluation; Learning -- Evaluation; Educational change; Professional education; Teachers -- Training of